Collective cancer cell invasion in contact with fibroblasts through integrin‐α5β1/fibronectin interaction in collagen matrix. Issue 12 (12th October 2020) - Miyazaki, Kaoru; Togo, Shinsaku; Okamoto, Reiko; Idiris, Alimjan; Kumagai, Hiromichi; Miyagi, Yohei
Abstract: Interaction of cancer cells with cancer‐associated fibroblasts (CAFs) plays critical roles in tumor progression. Recently we proposed a new tumor invasion mechanism in which invasive cancer cells individually migrate on elongate protrusions of CAFs (CAF fibers) in 3‐D collagen matrix. In this mechanism, cancer cells interact with fibronectin fibrils assembled on CAFs mainly through integrin‐α5β1. Here we tested whether this mechanism is applicable to the collective invasion of cancer cells, using two E‐cadherin‐expressing adenocarcinoma cell lines, DLD‐1 (colon) and MCF‐7 (breast). When hybrid spheroids of DLD‐1 cells with CAFs were embedded into collagen gel, DLD‐1 cells collectively but very slowly migrated through the collagen matrix in contact with CAFs. Epidermal growth factor and tumor necrosis factor‐α promoted the collective invasion, possibly by reducing the E‐cadherin junction, as did the transforming growth factor‐β inhibitor SB431542 by stimulating the outgrowth of CAFs. Transforming growth factor‐β itself inhibited the cancer cell invasion. Efficient collective invasion of DLD‐1 cells required large CAF fibers or their assembly as stable adhesion substrates. Experiments with function‐blocking Abs and siRNAs confirmed that DLD‐1 cells adhered to fibronectin fibrils on CAFs mainly through integrin‐α5β1. Anti‐E‐cadherin Ab promoted the single cell invasion of DLD‐1 cells by dissociating the E‐cadherin junction. Although the binding affinity of MCF‐7 cells to CAFs was lower than DLD‐1, they also collectively invaded the collagen matrix in a similar fashion to DLD‐1 cells. Our results suggest that the direct interaction with CAFs, as well as environmental cytokines, contributes to the collective invasion of cancers. Abstract : This study established a simple collective cancer invasion model in which E‐cadherin‐expressing cancer cells collectively invaded the collagen matrix in contact with bundles of cancer‐associated fibroblast fibers through integrin‐α5β1/fibronectin interaction. The results suggest that the fibrosis and environmental cytokines contribute to the collective invasion of cancers in vivo.